ALTERATIONS IN PARATHORMONE, CALCIUM AND PHOSPHORUS LEVELS IN CKD PATIENTS ON MAINTENANCE HAEMODIALYSIS IN A HOSPITAL SETTING IN PUNJAB.â€ - Bansal, Babita; Gahlot, Sushila; Prasher, P K; Takkar, Jaspreet (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Many people who have severe chronic kidney disease (CKD) will eventually develop kidney failure and will require dialysis. The control of parathormone (PTH), phosphorus, and calcium metabolism is one of the objectives in an adequate dialysis protocol. Therefore, we conducted this study to describe alterations in PTH, calcium, and phosphorous homeostasis in patients with CKD on hemodialysis in our center. Our study also aimed to find an association between hormonal and biochemical abnormalities in CKD patients, who have been on hemodialysis for â‰¥5 months and comparing the results obtained with that recommended by Kidney Disease Improving Global Outcomes (KDIGO) guidelines. Methods: This was a hospital-based cross-sectional observational study. The study population of 330 patients (>18 years) on maintenance hemodialysis coming to dialysis Unit of Department of Medicine of Gian Sagar Hospital, Ramnagar (Patiala), over a period of 3 years (2012-2015), were enrolled in the study. Each patient was considered only once for the study. In addition, biochemical analysis of serum intact PTH (iPTH), corrected calcium, phosphorus, total alkaline phosphatase (tALP), serum creatinine, blood urea, serum albumin, and hemoglobin of all cases was done using fully automated equipment. All statistical analyses were performed using SPSS statistical software, version 17. Results: The study population of 330 patients comprised adults, mainly illiterate (54.5%) predominantly belonging to the rural (66.4%) strata with a mean age of 52.67Â±15.05 (range: 25-98 years). The abnormality in the laboratory profile of the patients was found to be hyperparathyroidism in 40.3% as compared to hypoparathyroidism in 33.5% and normal iPTH levels in 26.2%. Hypocalcaemia was detected in 50.6% and hyperphosphatemia in 62.1% of the patients. There was statistically significant association of serum iPTH, with corrected calcium and phosphorus (P=0.032 and P=0.035, respectively). Corrected calcium was also significantly associated with phosphorus (P=0.001) and tALP (P=0.007). Conclusion: We showed in the present study that disorders of mineral metabolism are common in hemodialysis patients and that only a small proportion adheres to the targets as advised in the KDIGO guidelines for bone metabolism and disease in CKD. We demonstrated that these disorders are associated with important negative clinical outcomes, such as increased all-cause lack survival, more muscle and bone problems. Our findings, therefore, support a strict control of mineral metabolism in dialysis patients. Further research and progress in this area are required to establish a more rational approach with a view toward improving patient outcomes. Keywords: Parathormone, Calcium, Phosphorus, Hemodialysis. Â